MANAJEMEN KREATIVITAS UNTUK GURU PENDIDIKAN AGAMA ISLAM DALAM PENERAPAN PAIKEM (PEMBELAJARAN, AKTIF, INOVATIF, KREATIF DAN MENYENANGKAN) DI KELAS IX SEKOLAH MENENGAH PERTAMA NEGERI 3 KEC BATANG ASAM KAB TANJUNG JABUNG BARAT - Madyan Madyan; Ferdi Dwi Novanto; Dias Edmilizar; Sundari Sundari; Nur Sarifa Aini (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Education is the key to all quality progress and development, because with education humans can realize all their potential both as individuals and as citizens of society. The low quality of the teaching and learning process and outcomes indicates that the interaction between students and learning resources, such as teachers and the environment, is not effective so that the learning outcomes achieved are not optimal, resulting in low educational quality. Education is a process for someone to gain knowledge, experience and behavior. Apart from that, the role of education is also an important factor in a person's ability to solve problems in their life with the values ​​in society.